EVALUATION OF THE EXISTENCE OF Shorea platyclados Slooten ex Endert IN THE BUKIT DAUN PROTECTED FOREST - Marfuah Wardani; Adi Susilo (Pusbindiklat - LIPI, 2017)
Study on the evaluation of the existence of Shorea platyclados Slooten ex Endert (meranti bukit, meranti gunung, meranti tenam) on its natural habitat was conducted on May 2014 in Bukit Daun Protection Forest, Central Bengkulu District, Bengkulu. Exploration and inventarisation were designed in a semi-permanent plot, in which S. platyclados is used as the center of circle plot for vegetation analysis. Results showed that the distribution of S. platyclados is clump on steep valley, with its altitude is in between 400 – 600 m asl. Shorea platyclados was a dominant species on tree stage with good regeneration in all stage with IVI = 88.00%. Pole stages were dominated by Lindera subumbelliflora (Blume) Kostermans with IVI =10.58%, and seedling stage was dominated by Syzygium cymosum DC. with IVI =7.48%. The existence of S. platyclados in Bukit Daun Protected Forest, Central Bengkulu District was not endangered.